Pediatric recurrent respiratory tract infections: when and how to explore the immune system? (About 53 cases) - El-Azami-El-Idrissi, Mohammed (Pan Afr Med J, 2016)
Recurrent respiratory tract infections are one of the most frequent reasons for pediatric visits and hospitalization. Causes of this pathology are multiple ranging from congenital to acquired and local to general. Immune deficiencies are considered as underlying conditions predisposing to this pathology. Our work is about to determine when and how to explore the immune system when facing recurrent respiratory infections. This was based on the records of 53 children hospitalized at the pediatrics unit of Hassan II University Hospital, Fez Morocco. Thirty boys and 23 girls with age ranging from 5 months to 12 years with an average age of 2 years were involved in this study. Bronchial foreign body was the main etiology in children of 3 to 6 year old. Gastro-esophageal reflux, which in some cases is a consequence of chronic cough, as well as asthma were most frequent in infants (17 and 15% respectively). Immune deficiency was described in 7.5% of patients and the only death we deplored in our series belongs to this group. Recurrent respiratory tract infections have multiple causes. In our series they are dominated by foreign body inhalation and gastroesophageal reflux, which in some cases is a consequence of a chronic cough. Immune deficiency is not frequent but could influence the prognosis. Therefore immune explorations should be well codified.